The Role of Sustainable Business Practices in Achieving the SDGS: a Case Study of Rural Agricultural Communities - Zaenal Muttaqin; Deasy Silvya Sari (PT Publikasiku Academic Solution, 2023)
Villages have a strategic role as the smallest locus of development to support the achievement of Sustainable Development Goals (SDGs). It is focused on accelerating the achievement of SDGs by restoring the national economy. Therefore, in accelerating the achievement of sustainable development goals (SDGs), a practical role of sustainable business is needed for agricultural village communities. The method in this study is a qualitative method with an analytical descriptive approach, The data source is Library Research and other supporting literature, associated with phenomena that occur in the past, present and future. The results of this study are 1) The application of sustainable business model practices is one form of commitment of business people who are applied by having ethical governance and always contributing to economic development and not neglecting the quality of life of the workforce, local communities and surrounding communities 2) Obstacles in the implementation of Sustainable Development Goals in agricultural village communities include lack of effective land, lack of human resources, facilities, and government participation 3) Strategies in the role of agricultural village community development including Streamlining existing land, providing facilities and infrastructure, increasing human resources and optimal government participation